2018
DOI: 10.1002/2017ja024955
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Altitude Ion Heating, Downflowing Ions, and BBELF Waves in the Return Current Region

Abstract: Heavy (O+) ion energization and field‐aligned motion in and near the ionosphere are still not well understood. Based on observations from the CAScade, Smallsat and IOnospheric Polar Explorer (CASSIOPE) Enhanced Polar Outflow Probe at altitudes between 325 km and 730 km over 1 year, we present a statistical study (24 events) of ion heating and its relation to field‐aligned ion bulk flow velocity, low‐frequency waves, and field‐aligned currents. The ion temperature and field‐aligned bulk flow velocity are derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 78 publications
1
58
0
Order By: Relevance
“…Third, O + , if present, will escape if Xe + can escape. O + is a better carrier for Xe + escape than H + owing to its greater mass, it should be able to ionize Xe by charge exchange, and it is known to escape from Earth today (Shelley et al, 1972), although it is not known how (Shen et al, 2018). Considerable O + escape would imply less oxidation of Earth, but if the presence of O + were the signal of considerable amounts of O 2 (Mendillo et al, 2018), there would be few Xe + ions present and escape of Xe would be negligible.…”
Section: Other Omissions and Future Directionsmentioning
confidence: 99%
“…Third, O + , if present, will escape if Xe + can escape. O + is a better carrier for Xe + escape than H + owing to its greater mass, it should be able to ionize Xe by charge exchange, and it is known to escape from Earth today (Shelley et al, 1972), although it is not known how (Shen et al, 2018). Considerable O + escape would imply less oxidation of Earth, but if the presence of O + were the signal of considerable amounts of O 2 (Mendillo et al, 2018), there would be few Xe + ions present and escape of Xe would be negligible.…”
Section: Other Omissions and Future Directionsmentioning
confidence: 99%
“…This limited survey suggests that it may play a role during some, but not all, periods of auroral activity. Shen et al () observed significant ion‐electron heating as low as 350‐km altitude, noting that there had not been previous observations of heating at such low altitudes. The observations presented in this work suggest that such heating may extend even lower than previously thought, although, as discussed below, there are several other potential factors that may cause or contribute to the discrepancies observed during active periods, making it difficult to differentiate ion‐electron heating from other possible effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus is on singly charged ions as they represent the primary, most statistically significant component of ionospheric outflow, but note that not all ions flowing out of planetary ionospheres or escaping magnetospheres are singly charged; some are doubly and possibly triply charged. Now, nearly a quarter of a century later, although continual research (e.g., Andersson et al, 2004;Foss et al, 2017;Haaland et al, 2012;Moore et al, 2014;Ogawa et al, 2010;Peterson et al, 1994;Redmon et al, 2014;Seki et al, 2019;Shen et al, 2018;Skjaeveland et al, 2014;Strangeway et al, 2005;Wilson et al, 2004;Yau et al, 1993Yau et al, , 2011Yu & Ridley, 2013) has clarified much about thermospheric/ionospheric ion upflow, downflow, outflow, and chemistry, there is still much to be learned. That Earth's ionosphere contributes significantly to its magnetospheric O + and H + ion populations known from persistent investigation and repeated observation (see e.g., Moore et al, 2014;Shelley et al, 1972;Strangeway et al, 2005;Yau et al, 1993Yau et al, , 2011Yau et al, , 2012, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…That is, beyond the overview of the Yau et al (1993) data by Peterson et al (1994) and the very recent high-altitude measurements by Foss et al (2017) and the ring current measurements by Seki et al (2019), there has been little resolution of the vertical interactions affecting ions during outflow. For example, in the recent statistical study by Shen et al (2018) of electromagnetic-wave-related ion heating at~350-700-km altitude, the majority of ionospheric ion heating events were found to be associated with core ion downflows rather than upflows. For example, in the recent statistical study by Shen et al (2018) of electromagnetic-wave-related ion heating at~350-700-km altitude, the majority of ionospheric ion heating events were found to be associated with core ion downflows rather than upflows.…”
Section: Introductionmentioning
confidence: 99%